The effect of seed quality and health on onion cultivars establishment and yield - B. Darvishi; Jafar Ghasemi Ranjbar; Hasan Noorinejad; Samad Mobasser (علوم و فناوری بذر ایران)
This study was conducted to evaluate the health and quality of onion seeds that were submitted to Seed and Plant Certification and Registration Institute (SPCRI) in 2016-2017 for obtaining a certificate. For this purpose, the germination rate and seed vigor of 9 onion cultivars were evaluated in the seed quality analysis laboratory. Botrytis allii infection was assessed in the second part of onion seed samples based on Blatter method. Third part of onion seeds was cultivated based on a completely randomized block design with 3 replications in two regions (Karaj and Dezfoul) and two years. Gray rot prevalence in field and its effect on seedling emergence and yield was investigated. Results showed that seed germination of different onion cultivars were significantly different from each other. Also, cold and accelerated aging treatment significantly reduced germination of onion seeds. Seeds treated by carboxin thiram fungicide were free of gray rot, but untreated seeds were infected with an average of 1-4% of the causative agent. The level of infection was not related to onion seed germination, seedling field establishment and yield.